Evaluation of the success rate of pit and fissure sealants on first molars: 12 months follow‐up study. Issue 3 (11th January 2022) - Behroozian, Ahmad; Aghazadeh, Zahra; Sadrabad, Zahra Khalili; Aghazadeh, Marziyeh; Alizadeh, Vali; Esmaili, Zeynab; Pirzadeh Ashraf, Marzieh
Abstract: Introduction: Dental caries by far is the most prevalent concern of the preadolescents and adolescents in dental clinics. Despite the provision of local fluoride, the occlusal surfaces of teeth are susceptible to dental caries. Pit and fissure sealant therapy is a preventive method to decrease dental caries in permanent teeth. The present study aimed to evaluate the success of fissure sealant treatments of first molar teeth, at 3, 6 and 12 months follow‐ups. Materials and methods: Sixty‐five children were randomly selected. The subjects had already received fissure sealants in the department of public health dentistry. Demographic data, including age and gender, sealant failure and the type of failure were recorded in the relevant checklists. Feigal criteria were used to evaluate the success or failure of fissure sealant treatments. Results: Overall success rate was 74.3% for 1 year. Evaluation of the failure rate showed that at the 3‐month interval, 20.6% of the sealants exhibited failure (57.1% due to margin discoloration and 42.9% due to lack of margin adaptation). 28.6% of the sealants failed at the 6‐month (75% due to marginal discoloration and 25% due to anatomical form) and 41.2% failed at the 12‐month interval (57.1% due to marginal discoloration and 42.9% due to the lack of margin adaptation). Conclusion: The total failure rate of fissure sealant failures after 1 year was 27.7%. The most frequent reason for the failure of fissure sealants was marginal discoloration.